Palm Oil Industry Dynamics: Assessing P/B Ratios of Indonesian Palm Oil Companies through Palm Tree Profile, Average FFB Yield, and Palm Oil Extraction Rate - Hadi, Nixxen Dimitri; Handoko, Bambang Leo; Lindawati, Ang Swat Lin; Sarjono, Haryadi (Bright Publisher, 2025)
The primary objective of this paper is to explore the impact of palm tree profile (age), Fresh Fruit Bunch (FFB) yield, and Oil Extraction Rate (OER) on the Price-to-book (P/B) ratio of Indonesian palm oil companies listed on the Indonesia Stock Exchange (IDX) with return on equity (ROE) as a mediating variable. This study is important because it explores the variables that affect business valuations in a vital industry that employs more than 16 million people and generates huge export earnings, significantly supporting the Indonesian economy. Multiple linear regression is used in a quantitative analysis of secondary data gathered from the financial statements and annual reports of 15 palm oil enterprises from 2013 to 2023. The results show a strong positive relationship between OER and FFB yield with the P/B ratio, indicating that increased operational productivity and efficiency raise firm values. Specifically, the regression analysis revealed that each percentage point increase in OER is associated with a 0.1546 increase in the P/B ratio (p 0.001), and each unit increase in FFB yield contributes to a 0.1013 increase in the P/B ratio (p 0.001). On the other hand, the P/B ratio is negatively impacted by palm tree age, suggesting that older palms are less productive, with a coefficient of -0.1035 (p 0.001). The relationship between productivity ratio and valuation was also shown to be influenced by Return on Equity (ROE), which was identified as a mediating variable. The findings suggest that enhancing internal factors, such as plantation management and mill efficiency, can improve company valuation. It is recommended for future research to use larger sample sizes and longer observation periods to confirm these findings and explore additional variables.